EMPOWERMENT OF FARMERS THROUGH THE INDEPENDENT FARMERS PROGRAM IN BAURENO DISTRICT, BOJONEGORO REGENCY - Suprapti Ningsih; Ananta Prathama (DIA: Jurnal Administrasi Publik, 2021)
The agricultural sector is a sector that has a strategic role in the structure of national economic development, however, the agricultural sector has problems that need attention. In response to this, it is necessary to have a government role in reducing losses or overcoming the risk of crop failure which can be done through empowering farmers. The Bojonegoro Regency Government in empowering farmers has an incentive program in the form of an independent farmer program. The purpose of this study was to analyze and describe farmer empowerment through the independent farmer program in Baureno District, Bojonegoro Regency. This research uses descriptive qualitative research methods, with data collection techniques in the form of: observation, interviews, documentation. The results of this study, the farmers in Baureno District felt empowered by the empowerment carried out by the Bojonegoro Regency government through the independent farmer program which was analyzed by the theory of community empowerment stages: enabling, empowering and protecting.Keywords: Community empowerment, farmers, the independent farmer programs.